Maltol has anti-cancer effects via modulating PD-L1 signaling pathway in B16F10 cells - Han, Na-Ra; Park, Hi-Joon; Ko, Seong-Gyu; Moon, Phil-Dong (Frontiers in Pharmacology, 2023)
Among skin cancers, melanoma has a high mortality rate. Recent advances in immunotherapy, particularly through immune checkpoint modulation, have improved the clinical treatment of melanoma. Maltol has various bioactivities, including anti-oxidant and anti-inflammatory properties, but the anti-melanoma property of maltol remains underexplored. The aim of this work is to explore the anti-melanoma potential of maltol through regulating immune checkpoints. The immune checkpoint PD-L1 was analyzed using qPCR, immunoblots, and immunofluorescence. Melanoma sensitivity towards T cells was investigated via cytotoxicity, cell viability, and IL-2 assays employing CTLL-2 cells. Maltol was found to reduce melanin contents, tyrosinase activity, and expression levels of tyrosinase and tyrosinase-related protein 1. Additionally, maltol suppressed the proliferative capacity of B16F10 and induced cell cycle arrest. Maltol increased apoptotic rates by elevating cleaved caspase-3 and PARP. The co-treatment with maltol and cisplatin revealed a synergistic effect on inhibiting growth and promoting apoptosis. Maltol suppressed IFN-γ-induced PD-L1 and cisplatinupregulated PD-L1 by attenuating STAT1 phosphorylation, thereby enhancing cisplatin's cytotoxicity against B16F10. Maltol augmented sensitivity to CTLL-2 cell-regulated melanoma destruction, leading to an increase in IL-2 production.These findings demonstrate that maltol restricts melanoma growth through the down-regulation of PD-L1 and elicits T cell-mediated anti-cancer responses, overcoming PD-L1-mediated immunotherapy resistance of cisplatin. Therefore, maltol can be considered as an effective therapeutic agent against melanoma.